Sredine sredin - Razpet, Marko (Obzornik za matematiko in fiziko, 2012)
We discuss relations between some means related to rows and columns of matrices with positive real entries. We use the well-known inequality between arithmetic and geometric mean of positive real numbers.
Keywords: aritmetična sredina; geometrična sredina; harmonična sredina; matematika; mathematics; matrike; neenakosti